Smokeless tobacco control : report of a WHO Study Group, meeting held in Geneva from l to 6 June 1987 - WHO Study Group on Smokeless Tobacco Control; World Health Organization (Geneva : World Health Organization, 1988)
Issues an urgent call for action on the part of governments to ban or at least firmly curtil the use of smokeless tobacco before it is too late. Citing overwhelming scientific evidence linking use of smokeless tobacco products to cancer and other severe diseases, the report urges those responsible for public health to act immediately to stop both the increasing use of these products and the aggressive marketing that is promoting them. Throughout the report, an effort is made to help decision-makers and their advisers design national legislation that is strong enough and sufficiently comprehensive to counter the vigorous, inventive, targeted, and well-financed marketing of transnational tobacco companies. Readers are also reminded that if countries do not act now, tens of millions of children will become dependent on nicotine and the progress made in controlling tobacco smoking will be nullified by the diseases caused by smokeless tobacco.
1. Introduction -- 2. Chemical constituents, biochemistry and bioassays for carcinogenicity -- 3. Health effects -- 4. Prevalence, patterns and trends -- 5. Control strategies -- 6. Recommendations -- References -- Annexes
Keywords: Tobacco, Smokeless; Nicotine; Noncommunicable Diseases